Spatially adjusted determinants of Malaria and Anaemia Morbidity among children under age 5 years in Ghana, 2014 - Blam, Stephen Nuerteye (My University, 2018)
Background: Malaria and anaemia pose significant public health challenges to most developing countries. Sub-Saharan Africa continues to carry a disproportionately high share of the global malaria burden. Recent WHO (2015) global estimates on disease burden shows the African region accounted for 88% of the 214 million new malaria cases in 2015. This statistic further highlighted that the region accounted for 90% of malaria deaths in 2015. Similarly, anaemia, defined as low hemoglobin concentration, is estimated to globally affect 43% of children under five years of age. Anemia prevalence is very high among Ghanaian children under 5 years of age. The objectives of this study were to determine the prevalence and spatial distribution of malaria morbidity in children under age 5 years in Ghana in 2014, to ascertain the prevalence and spatial distribution of childhood anaemia morbidity in Ghanaian children under age 5 years in 2014, to determine the spatial distribution of factors associated with malaria morbidity in Ghana in 2014, and to determine the spatial distribution of factors associated with anaemia morbidity in Ghana in 2014. Objectives: The aim of the study is to determine spatial distribution and factors associated with malaria and anaemia morbidity among Ghanaian children under 5 years of age in 2014. Methods: This study analysed malaria and anaemia morbidity and prevalence using data from the Ghana 2014 Demographic and Health Survey. These data captured malaria related information on children under 5 years. Survey logistic and ordered logistic multivariable regression was done to determine associations between the singular outcomes malaria and anaemia and several explanatory variables. The regression models were employed and results thereof were used to produce maps illustrating the predicted risk of malaria and anaemia occurrence. The generalized linear mixed model was used to simultaneously identify the risk factors of malaria and anaemia of children under five years and how these are spatially distributed. Multilevel survey adjusted logistic and ordinal logistic regression models with non-spatial random effects were fitted for malaria and anaemia respectively. A Bayesian approach was employed to further adjust for spatial random effects on the convolution models for the two main outcomes. Results: The sample in this study was made up of 2727 children under age 5 years, of which 783 tested positive for malaria and 1873 had anaemia, resulting in an observed malaria and anaemia prevalence of 28.71% and 68.68% respectively. Spatially adjusted significant variables were: Child’s age; type of place of residence; mother’s highest education level, wealth index; child’s altitude adjusted haemoglobin level; cluster altitude; severe anaemia vomiting; severe anaemia extreme weakness. Children from the Western, Central, Greater Accra, Eastern, and Brong Ahafo regions were more likely to have malaria compared to northern region. Malaria was 1.46 times more likely to occur among children residing in rural than urban areas [OR=1.46, (95% CI: 1.02-2.16); p=0.05]. Vomiting as well as extreme weakness were 6.37 [OR=6.37 (95% CI: 2.16- 18.75); p<0.001] and 7.63 [OR=7.63 (95% CI: 3.02-19.22); p<0.001] times more likely to have anaemia than those without these symptoms. Children residing at higher altitude were 0.98 times less likely to have anaemia compared to those at lower altitude [OR=0.98 (95% CI: 0.97-0.99); p=0.01]. Conclusion: Recent reports in Ghana indicate that malaria and anaemia related deaths in children under age 5 years are on the ascendancy. In spite of this, there is a dearth of empirical research that establishes our understanding on the prevalence of malaria and anaemia in the endemic regions of Ghana. Understanding the prevalence of malaria and anaemia in terms of spatial risk factors, will provide more insight and practical guidelines to the formulation of policies aimed at fighting the spread of malaria and anaemia. Hence, directing health interventions to higher risk areas and ensuring nationwide coverage are promising strategies for promoting equity and reducing risk of malaria and anaemia. This study showed that Brong Ahafo, Eastern, Northern, Western, Volta and Upper East regions were the hotspot zones with greatest disease burden. Keywords: Ghana, Anaemia morbidity, Malaria morbidity, Malaria Indicator Survey (MIS), Demographic and Health Survey (DHS), spatial mapping, West Africa.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand in partial fulfilment of the requirements for the Degree of Masters in Epidemiology in the field Biostatistics and Epidemiology May, 2018.
Keywords: Malaria; Anemia; Pediatrics; Morbidity